ID 222 – Cortical markers of pain memorisation – A study with intra-cerebral recordings in Humans. Issue 3 (March 2016) - Chapon, A.; Perchet, C.; Garcia-Larrea, L.; Frot, M.
Abstract : This study proposes to highlight cortical regions involved in a short-term memory painful task, and their interactions by using intra-cerebral recordings from 10 epileptic patients. In order to emphasize pain memory specificity, three different stimulations were used: painful, somatosensory non-painful and auditory. Two different intensities were delivered in each condition, and patients had to compare stimulation from the previous one, delivered 8–10 s before. In a control task, patients had to read numbers on a screen between two stimuli, in order to ensure that they did not memorize anything about the stimulation. Data were analyzed in terms of evoked potentials and time frequency during retention phase. When painful stimuli had to be memorized, early components of evoked potentials showed an increased amplitude as compared to the control task, in regions involved in affective aspects of pain (anterior insula, prefrontal cortex). Moreover a specific late negativity was observed only for painful stimuli memorisation, which suggests an enhanced arousal. Time-frequency analysis showed an alpha desynchronisation in memory tasks during retention phase in regions involved in cognitive and affective dimensions of pain (anterior insula, anterior cingulate cortex, prefrontal cortex) which might be related to cognitive processing and mechanisms of attention.